Influence in-sourcing and outsourcing of consultants on construction project performance in Nigeria (Construction Economics and Building, 2011)
Research studies have discovered that outsourcing has several benefits and the practice is fast replacing in-sourcing especially with regard to construction consultants. In the attempt to examine the benefits of the two approaches on project outcome, this study investigates the influence of the use of in-sourced and outsourced consultants on project performance in Nigeria. The objectives are to determine the use of in-sourcing and outsourcing for selected consultants, compare the use of the two approaches in project delivery and their influence on project performance and compare the performance of projects in which in-sourced and outsourced selected consultants were engaged. To achieve these objectives, a questionnaire design approach was adopted. A field survey involving a sample of 164 projects were selected by stratified random sampling. Data were collected using structured questionnaires and analysed using percentage, mean, Spearman and t-tests. The results of the study reveal that clients engage both in-sourced and outsourced consultants in project development and that the practice has significant influence on project performance. It also discovered that the use of the two approaches has differing benefits on project delivery time and cost. The study concludes that in-sourcing and outsourcing are common practices in project development and that clients are facing a challenge in deciding which approach to adopt. The study also discovers that both approaches has benefits associated with project outcome and suggests that clients should consider these benefits in deciding in-sourced and outsourced consultants.